2009
DOI: 10.2355/isijinternational.49.1542
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Analysis of Flow Phenomenon in Centrifugal Flow Tundish

Abstract: Fluid flow phenomenon in Centrifugal Flow (CF) tundish is investigated using water modeling and numerical simulation techniques. The effect of the dam spacing and rotation speed on the flow structure has been analyzed in detail. Results reveal that the bias flow, originating from the rotary outflow, leads to the formation of transversal circulation behind the dam. Such transversal flow can effectively diminish the conventional dead volume. Meanwhile, small dam spacing helps to produce a large-scale transversal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Thirdly, the transient flow field and the temperature distribution of molten steel in tundish with induction heating are computed by adding the joule heating to energy conservation equation and the electromagnetic force to momentum conservation equation for molten steel as the source terms. 35,36) The governing equations of electromagnetic field and other physical fields are solved by employing the commercial software ANSYS and CFX, respectively. As for the electromagnetic field calculation based on ANSYS, the finite element method is used.…”
Section: Solution Methodsmentioning
confidence: 99%
“…Thirdly, the transient flow field and the temperature distribution of molten steel in tundish with induction heating are computed by adding the joule heating to energy conservation equation and the electromagnetic force to momentum conservation equation for molten steel as the source terms. 35,36) The governing equations of electromagnetic field and other physical fields are solved by employing the commercial software ANSYS and CFX, respectively. As for the electromagnetic field calculation based on ANSYS, the finite element method is used.…”
Section: Solution Methodsmentioning
confidence: 99%
“…1) only advisable in tundish with enough volume to sustain the side streams of the ports 2) refractory is easy to be eroded Swirling LS 9) 1) reducing the entry kinetic energy without promoting slag entrainment or vortexes 2) promote a recirculatory flow in the horizontal planes of the tundish 1) manufacturing difficulties for full-scale production 2) erosion problems 3) particles and impurities agglomeration 19) A bending nozzle 20) 17% increment of maximum swirling velocity in rotation chamber in centrifugal flow tundish to promote inclusion removal 1) only applicable in centrifugal flow tundish 2) the bend need to sustain high speed erosion Bell-shaped LS 21) 1) avoiding focused impact by enlarging outflow port area 2) greater plug volume to dead volume ratio limited twisted and jet deforming effect to control the bulk flow.…”
Section: Geometrical Descriptionmentioning
confidence: 99%
“…The progress in the solidification control has been made to obtain the refinement microstructure. The effects of the magnetic field [7], the convective flow [8], the gravity level [9] and the droplet interaction with the solidification interface [10] on the solidification process were investigated recently. It was indicated that the microstructure evolution is strongly dependent on the thermodynamics and kinetics of the liquid phase separation in the miscibility gap.…”
Section: Introductionmentioning
confidence: 99%